THE ROLE OF ENGLISH AS LINGUA FRANCA–INFORMED APPROACH IN ENGLISH LANGUAGE TEACHING AND LEARNING TO PRESERVE CULTURAL IDENTITY: FROM CLASSROOM TO PRACTICE - Simon Petrus Kita Ngatu (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2018)
The practice of teaching English as a global language that has been widely spread in Indonesia does not fit to promote Indonesian local culture. Most of English language teaching practice pay much attention to students’ understanding about their local culture, but the whole process of English language teaching (ELT) itself denotes that students do not really apply their local culture in English language learning. The effort of integrating local culture in ELT is still far from the concept of particularity, practicality, and possibility. This article provides a conceptual perspective on the role of English as Lingua Franca (ELF) – Informed Approach in ELT in terms of preserving students’ cultural identity. It starts by describing the important issues dealing with the topic, relating this study to previous studies to see the weaknesses and the strength, building an argument, and drawing conclusion and recommendation. The article concludes that the approach needs to be more informed in the whole process of ELT in terms of learning English and preserving students’ local culture in which students are allowed to use English within their local culture rather than only in understanding their culture without practicing.